Perceived Barriers to Trade Unionism in Malaysia - Ramasamy, Nagiah (2010)
Although trade unions in Malaysia generally play an important role in protecting the rights of workers, the movement is facing a declining trend. This study has examined the perceptions of workers, employers and trade union leaders on factors contributing to the decline of trade unionism in Malaysia. The central theme of the study was to identify the perceived barriers to trade unionism. Data was obtained through a structured questionnaire survey involving 859 employees, 429 employers and 182 trade union leaders. Further, in-depth interviews were conducted with union leaders, employers and the state to triangulate the results. The findings suggest that trade union decline is inevitable and trade unions do not seem to appeal to a large segment of the workforce. They not only perceive that unions have a negative image, but also that union membership may damage their career prospects. Unions appear to have limited power to maintain strong bargaining relationships with management, to organise new workplaces and to influence the need for union membership among new workers in existing workplaces. The current economic and political climate is further challenging the relevancy of trade unions. This study further suggests that the employer is a key determinant for trade union decline. Employers perceive trade unions as reducing their competitiveness. They also view trade union leaders and members unfavourably. While some employers appear to engage in union busting activities, a majority of employers attempt to influence workers’ values and perceptions by shifting towards HRM-type practices. This study concludes that employer opposition to unionisation as well as internal weaknesses within the trade union movement will mean that trade unions will struggle to collectivise in Malaysia. Leaders in companies, trade unions and the government need to discuss issues related to formation of trade unions, competitiveness of industry and legislation. Accessibility and availability of certain data from trade unions and employers are the main limitations. Based on the research findings, the theoretical and practical implications have been discussed. Suggestions for further research are also presented.